Optimasi Faktor Eksposi Teknik Pemeriksaan Radiografi Ossa Pedis dengan Computer Radiography di Instalasi Radiologi RSUD Dr. Ishak Umarella - Maritje S. J. Malisngorar; Akhmadi Akhmadi; Amelia Niwele (Asosiasi Riset Ilmu Kesehatan Indonesia, 2026)
Ossa pedis radiography is an important diagnostic procedure for evaluating fractures, structural abnormalities, and pathological conditions of the foot bones. Image quality is strongly influenced by exposure factors, particularly kilovoltage (kV) and milliampere-second (mAs), which must be optimized to ensure diagnostic quality while keeping radiation exposure as low as reasonably achievable. This study aimed to determine the optimal exposure factor combination for ossa pedis radiography using Computed Radiography (CR). An experimental design was applied with tube voltage fixed at 60 kV and mAs varied at 2, 3, 4, and 5 mAs. Radiographic examinations were performed using the anteroposterior (AP) projection according to standard procedures. Image quality was evaluated based on CR S-value and G-value parameters and visual assessment of density, contrast, and sharpness of bony anatomical details. The results showed that 60 kV and 4 mAs produced the best image quality, with S-value and G-value within the diagnostic range and an optimal balance of density, contrast, and anatomical sharpness. Therefore, 60 kV and 4 mAs is recommended as the optimal exposure setting for ossa pedis radiography using CR while supporting radiation dose optimization